Pengembangan Video Interaktif Persamaan dan Pertidaksamaan Linier Satu Variabel kelas VIII Berbasis Android - Kamelia, Nila Sa'idah; Farisi, Olief Ilmandira Ratu (Postulat : Jurnal Inovasi Pendidikan Matematika, 2025)
The aim of this research is to provide an Android based interactive video for the VIII grade that focuses on linear equations and inequalities in one variable. ADDIE (Analysis, Design, Development, Implementation, Evaluation) models is implemented in developing this media. After the media has been developed using GDevelop, a validation stage is carried out with experts and trials are carried out with students. Material experts' percentage results meet the "very valid" standard with 90%, while media experts' percentage results meet the "very valid" criteria with 85%. The student trial's findings demonstrated that this media is user-friendly and effective at enhancing comprehension of the subject matter. With an 84.05% percentage score on the student trial questionnaire, students responded favorably to this media. It demonstrated that the created media may be used as an educational tool to teach pupils about linear equations and inequalities in one-variable.